MAZAHIB AL-TAFSIR: DEFINISI, OBJEK KAJIAN, URGENSI, PERKEMBANGAN HISTORIS DAN EPISTEMOLOGINYA - Eva Aulia; Muhammad Izhar (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This article discusses the School of Tafsir as an important branch of the study of ‘Ulum Al-Qur’an ' which highlights the schools, styles, and tendencies of interpretation of the Qur'an from time to time. This study aims to explain the meaning of the School of Tafsir, its object of study, the factors behind the emergence of various schools of interpretation, and their significance in the study of interpretation. This research uses a qualitative method with a library research approach through analysis of various literature related to the science of interpretation and ‘Ulum Al-Qur’an . The results of the study indicate that the School of Tafsir is a discipline that has material objects in the form of interpretation products and the history of their emergence, and formal objects in the form of an analysis of the styles, methods, and ideological backgrounds of the exegetes. The diversity of schools of interpretation is influenced by internal factors such as the characteristics of the language and the content of the meaning of the Qur'an, as well as external factors such as political dynamics, theology, the development of science, and the socio-historical conditions of the Muslim community. Thus, the study of the School of Tafsir has an important role in enriching the treasury of Islamic knowledge, fostering a tolerant attitude towards differences in interpretation, and helping to understand the dynamics of Islamic thought in a more comprehensive and moderate manner.